Effect of Social Media Marketing Activities on Kahf Skincare Purchase Decisions, with Fear of Missing Out and Social Media Engagement as Mediating Variables - Anna Widiastuti; Ilham Maulana; Ali Ali (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of Social Media Marketing Activities (SMMA) on purchase decisions among consumers of Kahf skincare products, with Social Media Engagement (SME) and Fear of Missing Out (FoMO) serving as mediating variables. This study employs a quantitative approach, utilizing a data collection technique involving the distribution of questionnaires to Kahf consumers in Jepara Regency. The sampling technique used purposive sampling with a sample size of 180 respondents who had previously purchased Kahf products. Data were analyzed using the Partial Least Squares (PLS) method via the SmartPLS 4.0 application. The results indicate that Social Media Marketing Activities have a positive and significant effect on Social Media Engagement and Purchase Decisions. Additionally, Fear of Missing Out also has a positive and significant effect on Purchase Decisions. However, Social Media Engagement does not have a significant effect on Purchase Decision. These findings indicate that social media marketing activities can increase consumer engagement and trigger an emotional response in the form of FoMO, which ultimately drives the decision to purchase Kahf products. This study contributes to companies in designing more effective digital marketing strategies through the use of social media